Tracing British West Indian slavery laws - Collins, Justine K., author.
1 online resource.
Keywords: "This book provides a legal historical insight into colonial laws on enslavement and the plantation system in the British West Indies. The volume is a work of comparative legal history of the English-Speaking Caribbean which concentrates on how the laws of England served to catalyse the slavery laws and also legislation pertaining to post-emancipation societies. The book illustrates how these "borrowed" laws from England not only developed colonial slavery laws within the English speaking Caribbean but also inspired the slavery codes of a number of North American plantation systems. The cusp of the work focuses on the interconnectivities among the English-speaking slave holding Atlantic and how persons, free and unfree, moved throughout the system and brought laws with them which greatly affected the various enslaved societies"--